1998
DOI: 10.1093/oxfordjournals.molbev.a026013
|View full text |Cite
|
Sign up to set email alerts
|

A single base change altered the regulation of the Waxy gene at the posttranscriptional level during the domestication of rice

Abstract: The rice waxy (wx) locus has two functional alleles, Wxa and Wxb, which are defined by a large difference in the amount of the gene product, called Wx protein, that accumulates in mature seeds. To elucidate the molecular mechanism underlying this difference and to identify the base change causing the alteration of the regulation of the Wx gene during rice evolution, we determined the nucleotide sequences of the regulatory region of Wx alleles and analyzed their function in a transient assay system using rice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(128 citation statements)
references
References 26 publications
8
119
0
1
Order By: Relevance
“…Divergence between O. sati a ssp. japonica and indica at the waxy locus promoter is 0n83 % (Hirano et al, 1998). Isozyme data suggests that domesticated rice has roughly 71 % of the diversity of its wild relatives (Oka, 1988).…”
Section: How Has DI Ersity Changed During Domestication?mentioning
confidence: 99%
“…Divergence between O. sati a ssp. japonica and indica at the waxy locus promoter is 0n83 % (Hirano et al, 1998). Isozyme data suggests that domesticated rice has roughly 71 % of the diversity of its wild relatives (Oka, 1988).…”
Section: How Has DI Ersity Changed During Domestication?mentioning
confidence: 99%
“…Judging from the amylose content of the isogenic lines, Kikuchi (1988) suggested that Koshihikari, the most popular japonica rice variety in Japan, also harbours the Wx-b gene. Recently, sequence analysis of the wx locus has revealed that the low level of expression of the Wx-b gene results from a single nucleotide substitution at the 5′ splice site of the first intron (Cai et al 1998, Hirano et al 1998, Isshiki et al 1998, Wang et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…We saw panicle-cutting using hand-knife, and also saw a farmer to harvest directly only the seeds. According to Fukuta et al (1996) (Hirano et al, 1998; Issiki er at., 1998, G-T polymorphism). To apply the G-T polymorphism for waxy rice cultivars, we can estimate whether each waxy shain was derived from indica or japonica (Yamanaka et a1.,2002).…”
Section: Materials Ai{d Methodsmentioning
confidence: 99%